New Water Regimes - Alida Cantor (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Water resource management challenges around the world are not just hydrological issues-- they are socio-legal in nature as well. This edited collection critically examines legal and administrative structures of water control, with the goal of imagining alternatives to entrenched systems of capitalist and anthropocentric water governance. The collection contributes to the areas of legal geography and water resource governance. The research presented in the collection draws from numerous theoretical perspectives, including decolonial and post-anthropocentric approaches to water governance; social and environmental justice in water management; and understanding legal ecologies. The collection addresses a variety of themes of water governance, including water allocation, groundwater management, collaborative governance, drought planning, and water quality. The papers describe and analyze water issues and new ideas in multiple countries, including Australia, Ecuador, New Zealand, India, and the United States.